2001
DOI: 10.1002/eat.10002
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive‐behavioral model of bulimia nervosa: A direct evaluation

Abstract: The results suggest that the components of Fairburn's model may operate to maintain the bulimic cycle in a slightly different way to that originally proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
3
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 69 publications
7
34
3
1
Order By: Relevance
“…According to current theoretical models, ED patients judge their self-worth almost exclusively in terms of their shape and weight [46], and the emergence of BID issues seems to be associated with low self-esteem [3,44]. From this point of view, these data confirm the possibility that, for subjects who experienced an altered parental bonding, BID is strongly related to the lack of an autonomous sense of self and self-efficacy.…”
Section: Discussionsupporting
confidence: 76%
“…According to current theoretical models, ED patients judge their self-worth almost exclusively in terms of their shape and weight [46], and the emergence of BID issues seems to be associated with low self-esteem [3,44]. From this point of view, these data confirm the possibility that, for subjects who experienced an altered parental bonding, BID is strongly related to the lack of an autonomous sense of self and self-efficacy.…”
Section: Discussionsupporting
confidence: 76%
“…Dichotomous reasoning is indeed a common cognitive distortion among patients with AN and several studies have concluded that among patients with AN, dieting is not a necessary precondition for binge-eating in the absence of an all-ornothing reaction to the perceived violation of dietary restraint. 33 Interestingly, in our sample, this attitude seems to be distinctive, among obese patients, of those with BED, even if this finding needs to be replicated with a more thorough cognitive investigation. Note that the tendency to evaluate self-worth in terms of weight and shape and a dichotomous (black-and-white) thinking style, together with having unrealistic weight goals, low self-efficacy, poor coping, or problem-solving skills, has been identified as significant psychological predictors of weight regain in obesity.…”
Section: Resultsmentioning
confidence: 81%
“…Purgative behavior, however, is in itself a serious pathologic eating behavior and is a critical component in the development of BN (Byrne & McLean, 2002). Although we cannot be sure all persons in the purging group had BN, they did report problematic eating behavior strongly suggestive of BN.…”
Section: Discussionmentioning
confidence: 96%